Pre-War Small Town Middle Classes: What Happened to Them after the War (Szociológiai Szemle, 2024)
The ‘introduction’ of socialism to post World War Hungary (and elsewhere) led to a rapid and radical transformation of society. The expressed objective of the socialist government was the elimination of certain classes and the creation of a new elite. Every element of politics and power was mobilised towards this goal which involved such differing programmes as an administrative transformation of the economy and various kinds of negative and positive discrimination. The question is how far such ‘interference’ can reach into deeply rooted social processes to result in what a ‘social planner’ had scheduled for the longer run.We investigated what happened to the pre-war middle class of a small town from the thirties to the present, by tracing family histories.